Promotion and Service Quality on Students InDriver Decisions - Titin Khoerunnisa; Rizka Aula Assaf (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
The rapid advancement of digital technology has significantly transformed consumer behavior, particularly in the increased use of online transportation services such as InDrive. The intense competition in this industry compels companies to optimize promotional strategies and maintain service quality to influence consumers purchasing decisions. This study aims to analyze the effect of promotion and service quality on purchasing decisions among students using the InDrive application at the International Women University Bandung. A quantitative descriptive-verificative method was employed, and data were collected through questionnaires distributed to 92 respondents selected using purposive sampling. The data were analyzed using validity, reliability, classical assumption, and multiple linear regression tests at a 5% significance level. The results reveal that promotion has a significant effect on purchasing decisions, while service quality exerts a stronger and more dominant influence. This study concludes that effective promotional strategies combined with optimal service quality can strengthen consumer trust and purchasing decisions for application-based online transportation services. Keywords: Promotion; Service Quality; InDrive; Consumer Behavior; Customer Loyalty